Settlement of Estate Disputes in Review From a Legal Anthropological Perspective - Alim Tombili (Universitas Negeri Gorontalo, 2022)
This study aims to find out how the settlement pattern is used in the division of inheritance property in North Tamaila village and what factors are obstacles at the time of the division of inheritance property. Emperis type of research with a Case approach. result research shows the pattern of dispute resolution through several stages, the first stage which is known as